Optimización de espacios públicos, áreas verdes y administrativas mediante el rediseño arquitectónico sostenible del palacio municipal del GAD del cantón Urdaneta provincia de Los Ríos - Guzmán Lara, Dario Xavier (2016)
The Municipal Palace Urdaneta Canton is one of urban public facilities in the area, which has been affected by population growth, finding out rates allowed occupation, causing limitations construction areas to cover both administrative needs as the user, it is becoming dysfunctional, lacking technical and aesthetic design for the proper development of their activities. The City Council has developed the budgetary management for expansion and optimization of the GAD Municipal, with the area and necessary infrastructure. According to the current survey the Municipal Palace, it is implemented on uneven ground of 2210 m2, developed in an area of approximately 604.32 m2, generating free space, having a remaining useful life, being able to optimize their structures reducing costs synergy in their implementation, having the endorsement of the Municipal GAD, which have provided preliminary information and facilities to develop the various analysis and field research, thus achieving a viable proposition……